Fluorinated materials for energy conversion - Nakajima, Tsuyoshi, 1943-; Groult, Henri (Elsevier, 2005)
Fluorinated materials for energy conversion offers advanced information on the application of fluorine chemistry to energy conversion materials for lithium batteries, fuel cells, solar cells and so on. Fluorine compounds and fluorination techniques have recently gained important roles in improving the electrochemical characteristics of such energy production devices. The book therefore focuses on new batteries with high performance, the improvements of cell performance and the improvement of electrode and cell characteristics. The authors present new information on the effect of fluorine and how to make use of fluorination techniques and fluorine compounds. With emphasis on recent developments, this book is suitable for students, researchers and engineers working in chemistry, materials science and electrical engineering. * Contains practical information, supported by examples * Provides an update on recent developments in the field * Written by specialists working in fluorine chemistry, electrochemistry, polymer and solid state chemistry.
Keywords: Electric power production from chemical action.; Electrochemistry, Industrial.; Fluorides.; elektronické knihy; electronic books